Keberhasilan koperasi simpan pinjam penerima dana bergulir agribisnis dan dampaknya terhadap pendapatan anggota koperasi di Provinsi Jambi - J. Ilyas M.; M. Rachmad R.; Selamet Rahmadi (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
The study aims to analyze: 1) factors that influence the volume of business of savings and loan cooperatives that receive the assistance of agribusiness revolving funds; 2) the influence of income of cooperative members and the remaining results of the business on the success of the savings and loan cooperative recipients of agribusiness revolving funds. The data used is sourced from the stakeholders of the Savings and Loan Cooperative, among others, the agency in charge of cooperatives and MSMEs in Jambi Province and the Cooperative receiving assistance for agribusiness revolving funds in Jambi Province. In addition, data also comes from members of cooperatives that receive agribusiness revolving funds. Data were analyzed using multiple linear regression models. The results of the study show that: 1) The cooperative business volume is significantly affected by the amount of own capital, the amount of agribusiness revolving funds while the guidance carried out by the relevant agency has no significant effect; 2) cooperative member income has a negative and significant effect on the success of the cooperative. Conversely, the remaining results of the business have a positive and significant effect on the success of the cooperative.